THE IMPLEMENTATION OF DRAMA TECHNIQUE IN ENGLISH LITERATURE CLASS - Meiga Ratih T. (Universitas Muhammadiyah Semarang, 2019)
Teaching English literature through drama makes students aware that “English is not just words, structures and idioms, but it is a lively, dramatic and versatile means of communication (Case and Wilson, 2003: 4). Learning English Literature by only reading and comprehending the content can causes boredom for most learners. Based on this situation , dialogue or drama performances has been a favourite technique or an alternative way in teaching English Literature. The dialogues of drama are selected from the plays of well known author or the students create their own plays based on the form of drama. For examples; Pantomime, Costume Drama, Melodrama and Comedy. The objectives of the study are to desribe the implementation of drama and dramatic activities in English Literature teaching, and to find out the students’opinion on the implementation of drama as a technique to teach English Literature. The study employs descriptive qualitative method by which data were collected through academic literature review, document analysis, observation, and questionnaire. From the study it is found that drama was the best alternative to facilitate learner to experience autonomous learning and give students more opportunity to learn Literature and perform their ability in front of the audience.